The Histone Methyltransferase SETDB1 Modulates Survival of Spermatogonial Stem/Progenitor Cells Through NADPH Oxidase - Li, Xueliang; Chen, Xiaoxu; Liu, Yingdong; Zhang, Pengfei; Zheng, Yi; Zeng, Wenxian (Frontiers in Genetics, 2020)
SETDB1, a histone H3 lysine 9 (H3K9) methyltransferase, is crucial in meiosis and embryo development. This study aimed to investigate whether SETDB1 was associated with spermatogonial stem cells (SSC) homeostasis. We found that knockdown of Setdb1 impaired cell proliferation, led to an increase in reactive oxygen species (ROS) level through NADPH oxidase, and Setdb1 deficiency activated ROS downstream signaling pathways, including JNK and p38 MAPK, which possibly contributed to SSC apoptosis. Melatonin scavenged ROS and rescued the phenotype of Setdb1 KD. In addition, we demonstrated that SETDB1 regulated NADPH oxidase 4 (Nox4) and E2F1. Therefore, this study uncovers the new roles of SETDB1 in mediating intracellular ROS homeostasis for the survival of SSC.